Russia's Billionaires - Treisman, Daniel (American Economic Review, 2016)
Using data collected by Forbes since the 1990s, I examine the emergence and survival of the super-wealthy in Russia over the past two decades and compare Russia's record to those of other countries. The major surge in the number of Russian billionaires came in the mid-2000s, mirroring the dynamic worldwide. While early billionaires were predominantly found in the oil, gas, metals, and banking sectors, the distribution has become more diverse, now including some in trade, real estate, chemicals, and information technology. Only a minority of today's Russian billionaires acquired significant assets in the privatization of the 1990s.